Cho $F(x)$ là một nguyên hàm của hàm số $f(x)=3x^2-\mathrm{e}^x+1-m$ với $m$ là tham số. Biết rằng $F(0)=2$ và $F(2)=1-\mathrm{e}^2$. Giá trị của $m$ thuộc khoảng
![]() | $(3;5)$ |
![]() | $(5;7)$ |
![]() | $(6;8)$ |
![]() | $(4;6)$ |
Chọn phương án B.
$\begin{aligned}F(x)&=\displaystyle\int\left(3x^2-\mathrm{e}^x+1-m\right)\mathrm{\,d}x\\ &=x^3-\mathrm{e}^x+(1-m)x+C.\end{aligned}$
Vì $F(0)=2$ nên $$0^2-\mathrm{e}^0+(1-m)\cdot0+C=2\Leftrightarrow C=3.$$
Vậy $F(x)=x^3-\mathrm{e}^x+(1-m)x+3$.
Lại vì $F(2)=1-\mathrm{e}^2$ nên $$2^3-\mathrm{e}^2+2(1-m)+3=1-\mathrm{e}^2\Leftrightarrow m=6.$$
Vậy $m\in(5;7)$.